Resistivity Value as Characteristics Of Majapahit Kingdom Era Red Bricks - Supriyadi Supriyadi; Nurul Priyantari; Rosaria Dwi Sukmadewi (UNEJ e-Proceeding, 2016)
The era of Majapahit kingdom is the most famous kingdom era in Indonesia. This is shown by many heritage sites in Indonesia, including some of the temples that have been found. generaly, the temples consists of red brick is visually the same as the other red brick. Contrain in identification of heritage site era is frequenly faced in escavation. In this research, red brick of Majapahit kingdom era will be characterise using resistivity value and compare to recent red brick. The red brick samples were taken from two temples in Jember, the Deres temple (the Beteng Site) and the temple in Wuluhan country. The research result that Majapahit kingdom era red brick has resistivity lower than recent red brick, 15.73 Ωm for the Beteng Site and 17,5 Ωm for the temple in Wuluhan country, whereas 22,56 Ωm for recent red brick. Therefore, red brick resistivity value can be use as characteristics to identify era of a heritage site, especially Majapahit kingdom era.